A review on indoor smart energy managemet system - Li, Woon Koay; Naif, Yasir Hashim (Penerbit Universiti Malaysia Pahang, 2017)
One of the best choices to reserve energy is converted the original home into an intelligent one or known as “Smart Home”. In this paper, a review on samart energy management system was presented. Various novel methods and technologies are being extensively explored.